Blended Learning and Higher Education: A Bibliometric Analysis - Cruz-Cárdenas, Jorge (2023)
Blended learning is defined as an educational model or a way of teaching that combines in-person education with online education. In recent years, due to its great potential, this type of teaching applied to higher education has aroused great interest on the part of professionals and academics. This growing interest has been reflected in the rapid growth in the number of publications on blended learning and higher education. This article seeks to contribute to the knowledge base by presenting an integrated overview of this growing body of literature, and to this end the authors use bibliometric techniques. As a basis for the analysis, 2,477 relevant articles in the Scopus database were selected. The descriptive results obtained show rapid growth in the number of articles published over the years, a dominance of publications associated with developing and emerging countries, and the leading role of social sciences. An analysis of the co-occurrence of terms allows us to establish four areas of interest: 1) Covid-19 and the challenges and opportunities it poses, 2) the effectiveness and performance of blended learning, 3) the organization and design of blended learning, and 4) the technological tools and forms of delivery of blended learning. An analysis of the overlay visualization of terms makes it possible to establish the evolution of the topics of interest in the research over the years. Initially, interest focused on issues relating to the organization and design of blended learning. Currently, interest is focused on Covid-19 and the challenges it poses.